Produksi Rumput Laut (Gracilaria verrucosa) Berdasarkan Perbedaan Jarak Tanam dan Bobot Bibit di Tambak Desa Tlogosadang, Kecamatan Paciran, Kabupaten Lamongan - Norma Aprilia Fanni; Agung Pamuji Rahayu; Endah Sih Prihatini (Institut Pertanian Bogor, 2021)
This study aims to determine the highest production of planting Gracilaria verrucosa wich is cultivated in the ponds of Tlogosadang Village, Paciran Sub-District, Lamongan District by treating different spacings and initial seed weights. The cultivation method used was longline with a distance of 25 cm between longlines. The treatments were given in the form of spacings of 10 cm, 20 cm, and 30 cm, while the treatments of seed weights were 50 g, 100 g, and 150 g. Treatments were carried out in a pond measuring 20x5 m with a water depth between 90-102 cm depending on the tides. Sampling was conducted every 7 days for 50 days of maintenance by weighed, controlled, and measurement water quality. Before planting seaweed, pond preparation were carried out which included drying, liming, fertilizing to filling the water. This study used a Completely Randomized Factorial (CRF) Design consisted of two factors, namely spacing and seed weight, each with three levels. Data analysis used One-Way ANOVA showed that the treatment of spacing and seed weight gave a very significant difference (P <0.01), so it was continued with the Orthogonal Polynomial Test to see trends. The test results showed that the highest seaweed production was found at a spacing of 20 cm and a seed weight of 50 g, namely 2423.7 g/m. The water quality as a support for the growth of seaweed measured during the study showed that the waters ware classified as good and suitable for the cultivation of Gracilaria verrucosa seaweed. Keywords: Gracilaria verrucosa, longline, seaweed, seed weight, spacing